Quantitative Methods for Plant Breeding - Suza, Walter; Lamkey, Kendall (Open textbook library., 2023)
This open textbook covers common statistics used in agriculture research, including experimental design in plant breeding and genetics, as well as the analysis of variance, regression, and correlation.